3D printing high interfacial bonding polyether ether ketone components via pyrolysis reactions. (15th January 2021) - Li, Qiushi; Zhao, Wei; Niu, Bingjie; Wang, Yiliang; Wu, Xinhui; Ji, Jiawen; Li, Yongxiang; Zhao, Tingting; Li, Han; Wang, Gong
Abstract: Recently, 3D-printed polyether-ether-ketone (PEEK) components have been shown to offer many applications in state-of-the-art electronics, 5G wireless communications, medical implantations, and aerospace components. Nevertheless, a critical barrier that limits the application of 3D printed PEEK components is their weak interfacial bonding strength. Herein, we propose a novel method to improve this unsatisfied situation via the interface plasticizing effect of benzene derivatives obtained from the thermal pyrolysis of trisilanolphenyl polyhedral oligomeric silsequioxane (POSS). Based on this method, the bonding strength of the filaments and interlayers of 3D-printed POSS/PEEK components can reach 82.9 MPa and 59.8 MPa, respectively. Moreover, the enhancing mechanism of the pyrolysis products derived from the POSS is characterized using pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS), Fourier transform infrared spectroscopy (FTIR), and X-ray computed tomography (X-CT). Our proposed strategy broadens the novel design space for developing additional 3D-printed materials with satisfactory interfacial bonding strength. Graphical abstract: Unlabelled Image Highlights: A novel strategy to improve the interfacial bonding strength of 3D-printed polyether-ether-ketone components via pyrolysis reaction was developed. Almost isotropy mechanical properties in X-Y plane and 59.8 MPa Z-direction bonding strength were reported. Higher top layer's temperatures showed a positive influence on interlayer bonding strength. The enhancing mechanism of polyhedral-oligomeric-silsequioxane was analyzed from microstructure and pyrolysis analyses.